2007
DOI: 10.1152/ajplung.00127.2006
|View full text |Cite
|
Sign up to set email alerts
|

Complement levels and activity in the normal and LPS-injured lung

Abstract: Complement, a complex protein system, plays an essential role in host defense through bacterial lysis, stimulation of phagocytosis, recruitment of immune cells to infected tissue, and promotion of the inflammatory response. Although complement is most well-characterized in serum, complement activity is also present in the lung. Here we further characterize the complement system in the normal and inflamed lung. By Western blot, C5, C6, and factor I were detected in bronchoalveolar lavage (BAL) at lower levels t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 52 publications
8
69
0
1
Order By: Relevance
“…Using TNF-a as an example, the network analysis showed that in addition to proinflammatory proteins, TNF-a interacted with bacterial opsonins (complement proteins, SFTPA), mediators of apoptosis (annexin A5, annexin A1), and proteins involved in lung repair (EGFR) (30)(31)(32). This suggests that TNF-a modulates pathways involved in innate immunity and repair in the lungs, in addition to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Using TNF-a as an example, the network analysis showed that in addition to proinflammatory proteins, TNF-a interacted with bacterial opsonins (complement proteins, SFTPA), mediators of apoptosis (annexin A5, annexin A1), and proteins involved in lung repair (EGFR) (30)(31)(32). This suggests that TNF-a modulates pathways involved in innate immunity and repair in the lungs, in addition to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Complement proteins (and their cleavage products) have been detected in human ALF obtained from healthy hosts, where complement levels differed from levels in human serum (Bolger et al 2007). Complement is a complex, highly regulated protein system with an essential role in host defense through bacterial lysis, stimulation of phagocytosis, recruitment of immune cells to infected/ damaged tissue, and promotion of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Complement protein levels were determined in ALF-L from old and young mice and adult and elderly humans by Western blotting. We focused primarily on the classical complement pathway as we and others have shown that components of the alternative complement pathway are at very low levels in ALF (Bolger et al 2007;Ferguson et al 2004). C2, C3, and C4 molecules were determined.…”
Section: Alf Cytokines Are Altered In Old Agementioning
confidence: 99%
See 2 more Smart Citations